(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Zakharova G. B. Scientific and theoretical substantiation of the concept of “the ability to self-cognitive activity of students”. Scientific and theoretical analysis of the literature, modern dissertation research on the formation of the skills of cognitive activities, cognitive independence and related problems has been performed in the article; matching and comparison of modern theoretical and pedagogical achievements on the basis of system-active approach allowed to give definition to the ability to self-cognitive activity of students.